Peran Media Digital Video Interaktif dalam Meningkatkan Pemahaman Materi IPS Peserta Didik di Madrasah Ibtidaiyah - Ulfatul Khasanah (MISOOL: Jurnal Pendidikan Dasar, 2019)
This study aims to analyze the role of interactive digital video media in improving students' understanding of Social Studies (IPS) material at Madrasah Ibtidaiyah (Islamic Elementary School). The research employed a literature study (library research) with a descriptive qualitative approach. Data were collected from various relevant literature sources, such as journals, books, and proceedings, and then analyzed using content analysis. The results reveal three main roles of interactive video: (1) as a conceptual transformation medium that concretizes abstract IPS material; (2) as a catalyst for active learning that encourages student participation; and (3) as a facilitator of differentiated learning. This media is proven effective in enhancing students' conceptual and contextual understanding through dynamic visualization and authentic contexts. Furthermore, interactive video also significantly increases learning engagement (behavioral, cognitive, and emotional) and motivation, both intrinsic and extrinsic, by fulfilling the psychological needs for autonomy, competence, and relatedness. The study concludes that interactive digital video media is an innovative strategy with great potential for optimizing student understanding and engagement in Social Studies learning at Madrasah Ibtidaiyah in the digital era.